Analysis Of the Criminal Offense of Hajj Quota Trading from the Perspective of Islamic Criminal Law - Putri Adzanni; Yayan Muhammad Royani; M. Yusuf Azazy (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study was motivated by the emergence of the practice of buying and selling Hajj quotas in Indonesia, which has the potential to undermine fairness in the national waiting list system and conflicts with provisions of positive law and Islamic legal values. This study aims to analyze the criminal act of buying and selling Hajj quotas based on Articles 116 and 123 of Law No. 8 of 2019 concerning the Implementation of Hajj and Umrah and to examine it from the perspective of Islamic criminal law. The study employs a normative legal approach using a descriptive-analytical method through legislative and comparative approaches. Data was obtained through a literature review of legislation, court decisions, legal literature, and relevant sources of Islamic law. The results of the study indicate that the practice of buying and selling Hajj quotas is a prohibited act and is subject to criminal sanctions in the form of imprisonment or a fine in accordance with statutory provisions. From the perspective of Islamic criminal law, this act can be categorized as a jarīmah ta’zir because it involves the acquisition of unlawful profit, the abuse of trust, and the potential to infringe upon the rights of the community. This study concludes that both positive law and Islamic law consistently prohibit the practice of buying and selling Hajj quotas to ensure justice, social order, and the public interest.